In memory of Sergey A. Gredeskul (1942–2023) - Freilikher, Valentin; Kagalovsky, Victor; Kivshar, Yuri; Pastur, Leonid (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2024)
Professor Sergey Gredeskul, our long-time colleague and friend, passed away on October 7, 2023, at the age of 81 (together with his wife, Dr. Victoria Gredeskul), who had also been a long-time member of B. Verkin Institute for Low Temperature Physics and Engineering of the NAS of Ukraine. The simultaneous death of this peaceful elderly couple was caused by a brutal terrorist attack by Hamas terrorists in the early morning of October 7, 2023. Sergey Gredeskul was a renowned theoretical physicist, an expert in the theoretical physics of disordered condensed media, including the spectrum of elementary excitations and the propagation of waves and particles in such media, resonance and optical properties of magnetic media, and optical solitons to name a few. He is the author of more than a hundred scientific publications, including the monograph “Intro[1]duction to the Theory of Disordered Systems” (State Prize of Ukraine, 1985). For many years, Sergey has been actively involved in the work of our Journal.